Adjuvant Chemotherapy for Patients with T2N0M0 NSCLC. Issue 10 (October 2016) - Morgensztern, Daniel; Du, Lingling; Waqar, Saiama N.; Patel, Aalok; Samson, Pamela; Devarakonda, Siddhartha; Gao, Feng; Robinson, Cliff G.; Bradley, Jeffrey; Baggstrom, Maria; Masood, Ashiq; Govindan, Ramaswamy; et al.
ABSTRACT : Background: : Adjuvant chemotherapy improves survival in patients with completely resected stage II and III NSCLC. However, its role in patients with stage IB NSCLC disease remains unclear. We evaluated the role of adjuvant chemotherapy in a large data set of patients with completely resected T2N0M0 NSCLC. Methods: : Patients with pathologic stage T2N0M0 NSCLC who underwent complete (R0) resection between 2004 and 2011 were identified from the National Cancer Data Base and classified into four groups based on tumor size: 3.1 to 3.9 cm, 4 to 4.9 cm, 5 to 5.9 cm, and 6 to 7 cm. Patients who died within 1 month after their operation were excluded. Survival curves were estimated by the Kaplan‐Meier product‐limit method and compared by log‐rank test. Results: : Among the 25, 267 patients who met the inclusion criteria, there were 4996 (19.7%) who received adjuvant chemotherapy. Adjuvant chemotherapy was associated with improved median and 5‐year overall survival compared with observation for all tumor size groups. In patients with T2 tumors smaller than 4 cm, adjuvant chemotherapy was associated with improved median and 5‐year overall survival in univariate (101.6 versus 68.2 months [67% versus 55%], hazard ratio [HR] = 0.66, 95% confidence interval [CI]: 0.61–0.72, p < 0.0001) and multivariable analysis (HR = 0.77, 95% CI: 0.70–0.83, p < 0.001) as well as propensity‐matched score (101.6 versus 78.9 months [68% versus 60%], HR = 0.75, 95% CI: 0.70–0.86; p < 0.0001). Conclusions: : In patients with completely resected T2N0M0, adjuvant chemotherapy is associated with improved survival in all tumor size groups. The benefit in patients with tumors smaller than 4 cm strongly suggests a role for chemotherapy in this patient population and counters its current status as an exclusion criteria for adjuvant trials.